Market Entry Strategy for a Start-Up Company to Germany - Holubová, Michaela; Král, Petr, 1979-; Olšanová, Květa; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2013)
The goals of my thesis are to present the researched company an analysis of a German market in a speed-reading industry, to discuss the correctness of company's hypotheses about the German market compared to the German reality, and to suggest a marketing strategy for the company's market entry supporting the selected market entry mode. In the first part, the theoretical section is introduced in which motives for foreign entry, followed by models of an environment analysis, of entry modes and of a customer analysis are described. These models are further used in the second part in which specifically speed-reading market in Germany and a German customer are analyzed. Based on the analyses, the market entry mode of the company is suggested, followed by the evaluation of the previously defined hypotheses regarding a German customer and a product, and, lastly, the next steps which the company should execute are proposed.
Vedoucí práce: Petr Král
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2014
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2014
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses